2014
DOI: 10.1063/1.4862995
|View full text |Cite
|
Sign up to set email alerts
|

Extended Maxwell-Garnett-Mie formulation applied to size dispersion of metallic nanoparticles embedded in host liquid matrix

Abstract: The optical properties of metallic spherical nanoparticles embedded in host liquid matrix are studied. Extended Maxwell-Garnett-Mie formulation which accounts for size dispersion, the intrinsic confinement, and extrinsic size effect, is proposed for the calculation of the effective dielectric function and absorption coefficient of size dispersion of colloidal solution of Au and Ag nanoparticles in water. We demonstrate that the size distribution induces an inhomogeneous broadening and an increase of the amplit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 35 publications
3
58
0
Order By: Relevance
“…(8) and (9) for several NP shape distributions. By considering that the NP size is higher than 5 nm, 17 the intrinsic confinement induced by the limitation of the electron mean free path can be neglected.…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…(8) and (9) for several NP shape distributions. By considering that the NP size is higher than 5 nm, 17 the intrinsic confinement induced by the limitation of the electron mean free path can be neglected.…”
Section: Simulationsmentioning
confidence: 99%
“…[13][14][15][16] This model was recently extended to describe the optical properties of spherical NPs distributed in size by averaging their polarizability. 17,18 However, preparation routes unavoidably conduct to NPs showing a shape distribution which induces drastic changes in the optical properties of NP assembly. [19][20][21][22] Indeed, by combining Gibbs free energy calculation to discrete dipole approximation, Noguez et al [23][24][25] have shown that the morphology and so the optical properties of NPs depend on the temperature used to synthesize them.…”
Section: Introductionmentioning
confidence: 99%
“…S1 mainly contains spherical NPs with a 8.4 nm mean diameter for which the intrinsic confinement can occur. 18 However, the model does not take into account this effect. The correlation matrix (not shown here) suggests that all the parameters are independent.…”
mentioning
confidence: 99%
“…Effective medium theories, which approximate the composite material as a homogeneous medium, enable the calculation of the complex effective dielectric function and require few computing resources. The Maxwell Garnett theory 18 was recently extended to describe the optical properties of spherical NPs distributed in size by averaging their polarizability. An extension of the effective medium theory was proposed by Bohren and Huffman 19 to take into account the shape distribution of spheroidal NPs.…”
mentioning
confidence: 99%
See 1 more Smart Citation